Job loss, informality, and the scarring effect in central java’s labor market - Sucihatiningsih Dian Wisika Prajanti; Euis Soliha; Tri Purwani; Dhea Rizky Amelia; Tania Wicaksana; Agni Alam Wijaya; Febyolla Putri Aninditya; Kinanthi Sukma Wening (Jurnal Ekonomi Indonesia, 2026)
This study examines labor market vulnerability in Central Java with a focus on job loss risk, post-layoff transitions, and job quality after recovery from shocks in labor-intensive industries. Using data from the August 2024 Sakernas survey and applying probit and Heckman selection models, the analysis reveals that shocks have multidimensional impacts. Workers in manufacturing are more exposed to job loss compared to those in agriculture, while service sector workers are relatively more protected. Spatial patterns indicate that neighboring regencies of the shock epicenter (shock_sritex) face lower risks of layoffs, yet sectoral linkages heighten the vulnerability of workers in supporting industries such as trade and transportation. Post-layoff transitions show that most workers return through informal employment, reflecting the limited absorptive capacity of the formal sector. In terms of job quality, informal workers are more likely to earn below the minimum wage and to experience excessive working hours, indicating a scarring effect. Conversely, higher education and union membership are protective, increasing the chances of obtaining decent wages. These findings highlight the importance of integrated labor market policies that strengthen industry-based training, ensure wage protection, enforce working time regulations, and enhance cross-regional coordination to sustain employment in the aftermath of industrial shocks.